USP12 translocation maintains interferon antiviral efficacy by inhibiting CBP acetyltransferase activity. - Jin Liu; Lincong Jin; Xiangjie Chen; Yukang Yuan; Yibo Zuo; Ying Miao; Qian Feng; Hongguang Zhang; Fan Huang; Tingting Guo; Liting Zhang; Li Zhu; et al. (PLoS Pathogens, 2020)
CREB-binding protein (CBP) participates in numerous transcription events. However, cell-intrinsic inhibitors of CBP are poorly defined. Here, we found that cellular USP12 interacts with the HAT domain of CBP and inhibits CBP's acetyltransferase activity. Interestingly, USP12 positively regulates interferon (IFN) antiviral signaling independently of its deubiquitinase activity. Furthermore, we found that in IFN signaling USP12 translocates from the cytoplasm to the nucleus. The decrease in cytoplasmic USP12 facilitates CBP-induced acetylation and activation of IFN signaling proteins in the cytoplasm. Moreover, USP12 accumulation in the nucleus blocks CBP-induced acetylation of phosphorylated STAT1 (p-STAT1) and therefore inhibits the dephosphorylation effects of TCPTP on p-STAT1, which finally maintains nuclear p-STAT1 levels and IFN antiviral efficacy. USP12 nuclear translocation extends our understanding of the regulation of the strength of IFN antiviral signaling. Our study uncovers a cell-intrinsic regulation of CBP acetyltransferase activity and may provide potential strategies for IFN-based antiviral therapy.